WOMEN, ENTREPRENEURIAL ACTIVITY AND TERRITORY: DIFFERENCES OR MYTHS? - Antonio Garcia-Tabuenca; Jose L. Crespo-Espert; Federico Pablo-Marti (European Regional Science Association (ERSA), 2010)
The earliest published study on entrepreneurial women is credited to Schwartz (1976). Subsequently, various female researchers (Hisrich and Brush, 1984; Cromie, 1987; Kaplan, 1988;) started to examine the possible differences that could be derived from gender. The analysis of the features of entrepreneurial women is now a subject of discussion due to the fact that the results obtained so far are not conclusive. While Hisrich and Brush find significant differences related to gender (attitudes, motives), Buttner and Rosen (1988) do not find disparities for being man or woman, but due to mere organisational questions such as the type of business. On the other hand, Gatewood, Brush et al. (2008) detail the differences and myths related to the growth - venture capital- of women's entrepreneurial activity. All things considered, the activity and behaviour of entrepreneurial women is still controversial as it is a relatively recent issue and one from which homogeneous results have not yet been obtained. Along these lines, new contributions in different societies and territorial areas - including regions- allow researchers to penetrate more profoundly into this subject matter and discover new ideas and conclusions that provoke academic debate and offer suggestions for new policies. This research, which at first provides a specific review of the most relevant literature, investigates the perception of Spanish entrepreneurial women's activity, not only concerning the characterisation of their personal features - using specific surveys-, but also from the perspective of their performance in the activity - by comparing the entrepreneurial results over a specific period, including an expansion stage and a (more recent) recession stage. Comparatively speaking, certain control groups of the whole economy are chosen, by regions and sectors, which allows a counterfactual methodology, and statistical and econometric methods are used to refine the analysis. The results and conclusions broaden the understanding of the facts and provide evidence of which could be considered to be differences and which remains to be seen as myths of the entrepreneurial development of women in a Mediterranean country.
Keywords: 330; entrepreneurial women; personal features; performance and results; NUTS-1 regions